Alteration in PI3K/mTOR, MAPK pathways and Her2 expression/amplification is more frequent in uterine serous carcinoma than ovarian serous carcinoma. Issue 2 (7th August 2015) - Mahdi, Haider; Xiu, Joanne; Reddy, Sandeep K.; DeBernardo, Robert
<x xml:space="preserve">Abstract</x> Objectives To compare the molecular profile of a large cohort of uterine papillary serous carcinoma (UPSC) and ovarian serous carcinoma (EOC‐S). Methods 628 UPSC and 5335 EOC‐S tumors were evaluated using a commercial multiplatform profiling service (CARIS Life Sciences, Phoenix, AZ). Specific testing performed included a combination of gene sequencing (Sanger, next generation sequencing), protein expression (IHC) and gene amplification (CISH or FISH). Results TP53 was the most commonly mutated gene in both UPSC and EOC‐S (76% vs. 69%, P = 0.03). UPSC were more likely to have mutation in PIK3CA (29% vs. 2%, P < 0.001), FBXW7 (12% vs. 1%, P < 0.001), KRAS (9% vs. 5%, P < 0.001) PTEN (7% vs. 1%, P < 0.001), and CTNNB1 (2% vs. 0%, P < 0.001) compared to EOC‐S. On the other hand, EOC‐S were more likely to harbor mutation in BRCA1 (20% vs. 9% P = 0.17) and BRCA2 (18% vs. 6% P = 0.09). HER2 gene amplification (17% vs. 4%, P < 0.001) and Her2/neu expression (10% vs. 2%, P < 0.001) were more frequent in UPSC than EOC‐S, respectively. Conclusion UPSC have a distinct mutation profile indicating higher activity of PI3K/AKT/mTOR, and MAPK pathways and Her2 expression/amplification but a trend toward lower frequency of alteration in homologous recombination pathway compared to EOC‐S. Targeted PI3K/AKT/mTOR inhibitors should be evaluated in UPSC. J. Surg. Oncol. 2015 111:188–194. © 2015 Wiley Periodicals, Inc.